Proposed Method to Solve Transportation Problem and Compare it With Some Initial Fesiable (Al-Mansour Journal, 2022)
In general Gradation transportation problem within operation research problems, the transportation model considered from sub-application important to linear programming. There is a great important for the transportation and effective role as an important pillar of the economic development of countries. to solve the problem of the transportation initial basic fesiable solution (I.B.F.S) is needed, and then to continue in the developing solution until reaching the better solution (less cost). there is no ending in theorems of finding best solutions until geating the optimal solution in order to take the convenient decision. the aim of this paper is to suggest a new method from by the researcher to find initial basic fesiable solution and then compare it with vogel's approaximation method and a nother methods to show the importance and the accuracy of the proposed method. through the findings of the researcher it turned out to be innovative method to give high-efficient results based on the total cost least and they approaching to the optimal solution.ء
Keywords: Transportation Problem; Initial Basic Fesiable Solution; Innovative Method; Less Total Cost